2018
DOI: 10.1021/acs.nanolett.8b03321
|View full text |Cite
|
Sign up to set email alerts
|

Stacking-Dependent Magnetism in Bilayer CrI3

Abstract: We report the connection between the stacking order and magnetic properties of bilayer CrI3 using first-principles calculations. We show that the stacking order defines the magnetic ground state. By changing the interlayer stacking order one can tune the interlayer exchange interaction between antiferromagnetic and ferromagnetic. To measure the predicted stacking-dependent magnetism, we propose using linear magnetoelectric effect. Our results not only gives a possible explanation for the observed antiferromagn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
571
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 602 publications
(611 citation statements)
references
References 49 publications
37
571
1
2
Order By: Relevance
“…First, with the devotion of substantial research efforts, a number of new 2DLMs can be explored, with notable discoveries benefiting both fundamental and applied studies of quantum science. For example, the emergence of 2D magnetic insulators (e.g., CrI 3 ) extends the possibilities of novel device applications, such as spin‐filters and valley manipulation, through vdW heterostructure engineering . Besides, similar emerging 2DLM systems of VSe 2 , VAgP 2 S 6 , CuCrP 2 S 6 , and MnPSe 3 have also aroused much attention due to their outstanding performances in building ferrovalley devices and spin electronics …”
Section: Outlook and Discussionmentioning
confidence: 99%
“…First, with the devotion of substantial research efforts, a number of new 2DLMs can be explored, with notable discoveries benefiting both fundamental and applied studies of quantum science. For example, the emergence of 2D magnetic insulators (e.g., CrI 3 ) extends the possibilities of novel device applications, such as spin‐filters and valley manipulation, through vdW heterostructure engineering . Besides, similar emerging 2DLM systems of VSe 2 , VAgP 2 S 6 , CuCrP 2 S 6 , and MnPSe 3 have also aroused much attention due to their outstanding performances in building ferrovalley devices and spin electronics …”
Section: Outlook and Discussionmentioning
confidence: 99%
“…Besides the experimental effort in exploring the 2D magnetism, recent theoretical investigations have shown a strong dependence of the magnetic interlayer coupling in CrI 3 on stacking structure. In particular, a rhombohedral stacking structure is predicted to favor a ferromagnetic interlayer coupling, whereas a monoclinic stacking structure is coupled antiferromagnetically . For bulk CrI 3 crystal, a structural phase transition from a low‐temperature rhombohedral structure to a high‐temperature monoclinic structure is known to exist at ~200 K .…”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 99%
“…In particular, a rhombohedral stacking structure is predicted to favor a ferromagnetic interlayer coupling, whereas a monoclinic stacking structure is coupled antiferromagnetically. [70][71][72][73] For bulk CrI 3 crystal, a structural phase transition from a low-temperature rhombohedral structure to a high-temperature monoclinic structure is known to exist at~200 K. 57 Recently, the magnetic structure due to spin-lattice coupling in bilayer CrI 3 has been studied by second harmonic generation (SHG) at low temperatures. 74 The authors observed giant nonreciprocal SHG originating from layered antiferromagnetic order, which breaks both the spatial-inversion and time-reversal symmetries.…”
Section: Cr-based Vdw Magnetsmentioning
confidence: 99%
“…According to the Mermin–Wagner theorem,18 2D long‐range FM order cannot exist in an isotropic magnetic system. Recently, people found that 2D layered CrI 3 ,19–27 Cr 2 Ge 2 Te 6 ,28 and CrSiTe 3 29 possesses intrinsic magnetocrystalline anisotropy against thermal fluctuations. However, the Curie temperatures of CrI 3 , Cr 2 Ge 2 Te 6 , and CrSiTe 3 are only dozens of Kelvins.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Mermin-Wagner theorem, [18] 2D long-range FM order cannot exist in an isotropic magnetic system. Recently, people found that 2D layered CrI 3 , [19][20][21][22][23][24][25][26][27] Cr 2 Ge 2 Te 6 , [28] and CrSiTe 3…”
mentioning
confidence: 99%